Die Typen der orientalischen, australischen und äthiopischen Acrolepiidae (Lepidoptera). - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1986)
Of the 16 so far as Acrolepiidae described species from the oriental, ethiopian and australian region could nine of them examined, from which one species not belongs to the family. From the other seven there was no material of types, so that the systematics position could'nt clarified.Nomenclatural Actscorticosa (Meyrick, 1913) (Acrolepiopsis), comb. n. hitherto Acrolepia corticosamanganeutis (Meyrick, 1913) (Acrolepiopsis), comb. n. hitherto Acrolepia manganeutisnephelota (Bradley, 1965) (Digitivalva (Digitivalva)), comb. n. hitherto Acrolepia nephelota